Transformasi Limbah Organik menjadi Pupuk Kompos sebagai Upaya Pemberdayaan Petani di Desa Bambang, Kecamatan Wajak, Kabupaten Malang: Transformation of Organic Waste into Compost Fertilizer as an Effort to Empower Farmers in Bambang Village, Wajak District, Malang Regency - Harry Putra, Dian Nugraha; Tri Rahardjo, Bambang; Supriyanto, Tomo Agus; Taufiqurrahman, Achmad Fitriadi; Sunarto, Bintar Probo; Hilmi, M. Aldian; Firdaus, Zulfan; Hamdani, Rizky Dwi (AGROINOTEK Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to empower farmers in Bambang Village, Wajak District, Malang Regency, to manage organic waste into compost as an effort to restore soil fertility in former sand-mining areas and promote sustainable agriculture. The program was carried out over two months, involving 20 farmers through three main stages: socialization, technical training, and evaluation. An educational-participatory approach was applied to enhance farmers’ knowledge and skills in compost production and application on horticultural land. The results showed a 40% increase in participants’ knowledge, successful production of high-quality compost, and noticeable improvements in soil structure after its application. In addition, farmers began reducing their dependence on chemical fertilizers and managing organic waste independently. This activity proved effective in improving farmers’ capacity while contributing to the rehabilitation of degraded land ecosystems and the development of sustainable agriculture in Bambang Village.